2021
DOI: 10.1038/s41598-021-02152-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gravity on respiratory kinematics during phonation measured by dynamic magnetic resonance imaging

Abstract: Respiratory kinematics are important for the regulation of voice production. Dynamic MRI is an excellent tool to study respiratory motion providing high-resolution cross-sectional images. Unfortunately, in clinical MRI systems images can only be acquired in a horizontal subject position, which does not take into account gravitational effects on the respiratory apparatus. To study the effect of body posture on respiratory kinematics during phonation, 8 singers were examined both in an open-configuration MRI wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, it cannot be completely excluded that the voice production mechanisms were influenced by the measurement conditions. Our working group revealed that also professionally trained singers show systematical effects of body positions leading to changes in respiratory kinematics (Traser et al, 2021b), vertical laryngeal position and vocal tract configuration (Traser et al, 2013). Thus, even if singers have been trained to accurately position the vocal tract and larynx during their Estill Voice Training ® education, there may be gravity-related differences between upright and supine Frontiers in Physiology frontiersin.org phonation.…”
Section: General Discussion Of Data Plausibility and Limitationsmentioning
confidence: 97%
“…Nevertheless, it cannot be completely excluded that the voice production mechanisms were influenced by the measurement conditions. Our working group revealed that also professionally trained singers show systematical effects of body positions leading to changes in respiratory kinematics (Traser et al, 2021b), vertical laryngeal position and vocal tract configuration (Traser et al, 2013). Thus, even if singers have been trained to accurately position the vocal tract and larynx during their Estill Voice Training ® education, there may be gravity-related differences between upright and supine Frontiers in Physiology frontiersin.org phonation.…”
Section: General Discussion Of Data Plausibility and Limitationsmentioning
confidence: 97%
“…Measurement points are defined in Table 3 . For best comparability these measures were selected based on existing literature on the subject ( Traser et al, 2017b , 2020a , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement points are defined in Table 3. For best comparability these measures were selected based on existing literature on the subject (Traser et al, 2017b(Traser et al, , 2020a(Traser et al, , 2021. (Bunch and Chapman, 2000), vital capacity (=VC), forced expiratory volume in 1 s (= FEV1), body height and body-mass-index (=BMI).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation